Effect of Synchronized Lifestyle Modification Program and Physiotherapy in Improving Type 2 Diabetic Neuropathy patients having Increased Body Mass Index - Rubab Rameez, Shazia Ali, Tayyaba Anis Chaudhry, Sidra Shaukat, Ayesha Zafar, Fatima Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Prevalence of diabetic neuropathy (DPN) is associated with increased Body Mass Index (BMI). Synchronized lifestyle modification program attempts to synchronize the circadian rhythm of the body through diet and exercise. Objective: Determine the role of Synchronized Lifestyle Modification Program (SLP) and Physiotherapy on fasting blood glucose (FBG), HbA1c, lipid profile, and degree of neuropathy in Type 2 DPN patients on Oral Hypoglycemic Agents (OHAs) having increased BMI. Materials and Methods: Randomized-controlled trial. Evaluation of 120 DPN patients on OHAs included, MNSI, BBS, FBG, HbA1c, Lipid profile and NCS. Participants divided into Group A and B, then divided into A1 and B1, that were overweight and A2 and B2, that were obese. B1 was divided into 1, 2 and 3 and B2 was divided into 4, 5 and 6. Groups 1 and 4 received SLP, Groups 2 and 5 received both SLP and Physiotherapy and Groups 3 and 6 received Physiotherapy for 12 weeks. p≤0.05 was considered significant. Results: MNSI, BBS, FBG, HbA1c, Total Cholesterol, TGs, HDL and LDL were significantly improved in Group 2. Conclusion: Combined Synchronized Lifestyle Modification Program and Physiotherapy is effective in DSPN patients that were overweight.